Asupan Energi, Karbohidrat, Serat, Beban Glikemik, Latihan Jasmani dan Kadar Gula Darah pada Pasien Diabetes Mellitus Tipe 2 - Fitri RI; Yekti Wirawanni (MEDIA MEDIKA INDONESIANA, 2012)
Energy intake, carbohydrate intake, fiber intake, glycemic load, exercise and blood glucose levels in patients with type 2 diabetes mellitusBackgrounds: The worldwide prevalence of type 2 diabetes mellitus (DM) is increasing at epidemic proportion. Dietary patterns and sedentary lifestyle are risk factors of type 2 DM.Objective: The study aimed to examine the association between carbohydrate intake, total energy intake, fiber intake, glycemic load, frequency of exercise and duration of exercise with fasting blood glucose levels and with 2h postprandial blood glucose levels. Method: In this observational study with crossectional approach, 46 adults with type 2 DM. The subjects consisted of 17 male and 29 female. This study was performed at Dr. Kariadi Hospital during February-March 2008. Data on food consumption was obtained using semi quantitative food frequency questionnaire (FFQ) and recall. Data on exercise was obtained using questionnaire. Data on blood glucose level was obtained from medical records. Data analysis used Pearson Product Moment and multiple regression to test this associations.Results: Most (76.1% and 78.3%) subjects had high fasting blood glucose and 2h pp. In bivariate analysis, significant associations with fasting blood glucose level were observed for carbohydrate intake (r=0.638, p=0.000), total energy intake (r=0.539, p=0.000), fiber intake (r=-0.670, p=0.000), glycemic load (r=0.345, p=0.019), frequency of exercise (r=-0.561, p=0.000), and duration of exercise (r=-0.393, p=0.007). Significant associations with 2h postprandial blood glucose level were also observed for total energy intake (r=0.673, p=0.000), fiber intake (r=-0.638, p=0.000), glycemic load (r=0.775, p=0.000), frequency of exercise (r=-0.482, p=0.001), and duration of exercise (r=-0.393, p=0.007). Fiber intake, frequency of exercise and duration of exercise were negatively associated with fasting blood glucose levels and with 2h postprandial blood glucose levels. Carbohydrate intake, total energy intake, fiber intake, glycemic load, frequency of exercise and duration of exercise influenced 69.7% fasting blood glucose levels and 71.3%2h blood glucose levels.Conclusion: The unsuccessful blood glucose level central are associated with food intake glycemic index of the food and physical activity.Keywords: Carbohydrate intake, total energy, fiber, glycemic load, exercise, blood glucose levels, type 2 diabetes mellitus ABSTRAKLatar belakang: Prevalensi diabetes mellitus (DM) tipe 2 meningkat secara epidemologis di seluruh dunia. Pola makan dan pola hidup santai merupakan faktor risiko DM tipe 2.Tujuan: Menjelaskan hubungan asupan energi, asupan karbohidrat, asupan serat, beban glikemik, frekuensi latihan jasmani dan durasi latihan jasmani dengan kadar gula darah puasa dan kadar gula darah 2 jam postprandial (2 jam pp).Metode: Penelitian ini bersifat observasional dengan pendekatan belah lintang dilaksanakan di Rumah Sakit Dr. Kariadi Semarang selama bulan Febuari-Maret 2008 dengan 46 pasien DM sebagai subyek penelitian, yang terdiri atas 17 orang laki-laki dan 29 orang perempuan. Data asupan makanan diperoleh dengan formulir frekuensi makan semi kuantitatif dan recall. Data latihan jasmani diperoleh dengan kuesioner. Data kadar gula darah diperoleh dari buku rekam medik. Analisis data menggunakan korelasiPearson Product Moment dan regresi linear ganda.Hasil: Sebagian besar (76,1%) dan (78,3%) subyek mempunyai kadar gula darah puasa dan 2 jam pp dengan kategori tinggi. Terdapat hubungan bermakna untuk kadargula darah puasa dengan asupan energi (r=0,539, p=0,000), karbohidrat (r=0,638, p=0,000), serat (r=-0,670, p=0,000), beban glikemik (r=0,345, p=0,019), frekuensi latihan jasmani (r=-0,561, p=0,000) dan durasi latihan jasmani (r=-0,393, p=0,007). Terdapat hubungan bermakna antara kadar gula darah 2 jam pp dengan asupan energi (r=0,673, p=0,000), asupan serat (r=-0,638, p=0,000), beban glikemik (r=0,775, p=0,000), frekuensi latihan jasmani (r=-0,482, p=0,001) dan durasi latihan jasmani (r=-0,393, p=0,007). Asupan energi, karbohidrat, serat, beban glikemik, frekuensi latihan jasmani dan durasi latihan jasmani secara bersama-sama mempengaruhi 69,7% kadar gula darah puasa, dan 71,3% kadar  gula darah 2 jam pp.Simpulan: Ketidakberhasilan pengendalian kadar gula darah berhubungan dengan asupan dan beban glikemik makanan serta aktivitas fisik yang rendah.